2021
DOI: 10.1155/2021/6814215
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Prophylactic Use of Plants Containing Saponin-Type Compounds as Antibiofilm Agents against Respiratory Tract Infections

Abstract: Epidemic diseases have been observed in every period of human history, and the treatment process has taken time. Causative microorganisms reproduce as biofilm and contribute to the emergence of various infectious diseases. The process that starts with respiratory disorders causes serious lung infections due to bacteria and viruses that accumulate and multiply. The biofilms are difficult to eliminate and show increased resistance to available antimicrobial agents. There is a need to identify and develop potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
1
2
0
1
Order By: Relevance
“…The terpenoids occur when the olfactory system is tied to emotional centers in the brain, so inhaling specific terpenoids can positively affect mood and an overall sense of well-being. Certain other terpenoids have been shown to have neurotherapeutic, anti-inflammatory, antioxidant, and pain-relieving benefits 27 . Saponins decrease blood lipids, lower cancer risk, and lower blood glucose response.…”
Section: Resultsmentioning
confidence: 99%
“…The terpenoids occur when the olfactory system is tied to emotional centers in the brain, so inhaling specific terpenoids can positively affect mood and an overall sense of well-being. Certain other terpenoids have been shown to have neurotherapeutic, anti-inflammatory, antioxidant, and pain-relieving benefits 27 . Saponins decrease blood lipids, lower cancer risk, and lower blood glucose response.…”
Section: Resultsmentioning
confidence: 99%
“…Its therapeutic activity has been linked to its ability to form complexes with soluble and extracellular proteins as well as bacterial cell walls [ 23 ]. Saponins are established antimicrobial agents as they can mediate the leakage of proteins and certain enzymes from invading pathogenic cells [ 24 ]. Besides, steroids possess antibacterial attributes as there is a relationship between membrane lipids and their sensitivity to steroidal compounds, which establishes the proposed mechanism of steroids’ antibacterial action via their association with membrane lipids to cause leakages from liposomes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saponins are characterized by wide antimicrobial activities that occur through various mechanisms associated with the assorted structures of saponin molecules. Studies have indicated that the activities of plant‐derived saponins in fighting infection are mediated by their detergent‐like activity, which leads to damage to the bacterial cell membrane, causing augmentation of ion permeability, damage to vital intracellular components, or interruption of bacterial protein synthesis 38 …”
Section: Discussionmentioning
confidence: 99%